Analysis of the Effect of Green Advertising and Green Innovation on the Purchase Intention of Environmentally Friendly Products Mediated by Knowledge of Environmentally Friendly Products - Nurcahya, Wilma Arum; Susila, Ihwan (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the use of green advertising and green innovation by companies to increase consumers' knowledge of green products, which will then influence consumers' green purchase intentions, in the context of environmentally friendly beauty products. In this study, data collection was conducted through an online survey using a questionnaire distributed to respondents containing questions about the variables involved. The sampling technique used was purposive sampling, which is a non-probability sampling technique. The respondents selected were consumers who use or are familiar with environmentally friendly beauty products. A total of 150 respondents were obtained in this study. Data was analyzed using PLS-SEM to validate the research construct model using the SmartPLS analysis software tool. The results of this study indicate that green advertising and green innovation have a positive and significant effect on green product knowledge and green purchase intention. Green product knowledge has a positive and significant effect on green purchase intention. Green advertising does not have a positive effect on green purchase intention.